2023
DOI: 10.1136/jnis-2022-019537
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravenous thrombolysis before endovascular therapy on outcomes in patients with large core infarct

Abstract: BackgroundThe safety and efficacy of bridging therapy with intravenous thrombolysis (IVT) and mechanical thrombectomy (MT) in patients with large core infarct has not been sufficiently studied. In this study, we compared the efficacy and safety outcomes between patients who received IVT+MT and those treated with MT alone.MethodsThis is a retrospective analysis of the Stroke Thrombectomy Aneurysm Registry (STAR). Patients with Alberta Stroke Program Early CT Score (ASPECTS) ≤5 treated with MT were included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Several other studies have reported similar results. 21 22 Anadani et al 22 conducted a research on patients with ASPECTS value ≤5 who underwent thrombectomy in the STAR trial. They used the propensity score matching method and found that the favourable outcomes (90-day mRS 0-2) and successful reperfusion rates were comparable between patients who underwent IVT and those who did not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies have reported similar results. 21 22 Anadani et al 22 conducted a research on patients with ASPECTS value ≤5 who underwent thrombectomy in the STAR trial. They used the propensity score matching method and found that the favourable outcomes (90-day mRS 0-2) and successful reperfusion rates were comparable between patients who underwent IVT and those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Some studies evaluated the effect of endovascular treatments alone on the prognosis of patients with large cerebral infarctions, however, obtained conflicting results. [21][22][23][24] It has remained controversial whether endovascular therapy alone benefits patients with large cerebral infarctions. Our study was derived from the ANGEL-ASPECT to demonstrate whether endovascular therapy, combined with IVT, was safe and effective in the patients with large infarctions due to cerebral large-vessel occlusion.…”
Section: What Is Already Known On This Topicmentioning
confidence: 99%
“…A retrospective study of 398 patients propensity matched in pairs under two groups of IVT before EVT versus EVT alone in patients with ASPECTS ≤5 did not show any significant difference in rates of any ICH or sICH between the two groups. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%